Mechanical performance of bamboo-inspired tapered hollow strut lattice structures fabricated by laser powder bed fusion (LPBF) - Yu Song; Zhenyu Chen; Tongzheng Wei; Chen Ge; Yuang Cheng; Ming Liu; Qingbo Jia (Advanced Manufacturing)
Drawing upon the intricacies of nature, bionics has significantly bolstered the engineering structure performance by providing innovative solutions and novel design principles. This study presented a tapered hollow strut lattice structure design that is inspired by the unique structural attributes of bamboo. The relative density, mechanical responses and Zenner’s anisotropy of the developed BCC, RD and OCTET unit cells with tapered hollow struts were simulated, while the corresponding geometric configurations that deliver the best combinations of physical and mechanical properties were optimized. The selected unit cells were then fabricated into 3 × 3 × 3 type lattice structures by laser powder bed fusion (LPBF) for experimental analysis. The compression results confirmed that the tapered hollow strut design obviously improved the deformation stability as compared with the straight hollow strut and solid strut design counterparts. Deformation modes analysis suggested that the tapered hollow strut design enhanced the strength and shear resistance, which contributed to the deformation stability improvement of the designed lattice structure. The current study is envisaged to provide useful guidance for future bio-inspired lattice structure design, with the final aim of enhancing the mechanical properties of the lightweight components.